Determinants of purchasing catastrophe insurance by communes – behavioural perspective - Gawin, Mateusz; Swacha-Lech, Magdalena (Determinanty nabywania ubezpieczeń katastroficznych przez gminy – perspektywa behawioralna)
The paper examines whether Polish communes are willing to buy catastrophe insurance considering behavioural factors such as heuristics and biases. The core methods used in this contribution involve a survey among 348 Polish communes in 2020. The necessary empirical data of a qualitative nature was collected by a consortium of two research agencies, Biostat Research & Development Sp. z o.o. and Biostat Sp. z o.o. The research results supported the hypothesis that the levels of commune income do not have a decisive impact on decisions about the purchase of insurance against catastrophic losses by Polish communes, which allowed to emphasize the role of behavioural aspects of the decision-making process. The article extends the BDM area to municipalities
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 1, s. 11-27